2016
DOI: 10.1177/0731684415627296
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid bonded-fastened joints and their application in composite structures: A general review

Abstract: Hybrid bonding-fastening is an alternative joining technique that consists of simultaneous adhesive bonding and mechanical fastening of the adherends. In this paper, pertinent scientific publications are selected and reviewed in an attempt to synthesize the current knowledge on various aspects of this technique. A particular focus is maintained on its application in composite structures. Two major bonding-fastening methods, namely bonding-bolting and bonding-pinning, are identified and contrasted, and the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 87 publications
(357 reference statements)
2
32
0
Order By: Relevance
“…This increase is not statically significant but indicates that there was no appreciable change in the joints' structural performance. However, the load-displacement curves exhibit a bi-linear response, reflecting a change in stiffness, and this behaviour is consistent with other published works on similar adhesive joints [33,19]. The second region with a lower slope can be attributed to the plastic deformation of the adhesive.…”
Section: Resultssupporting
confidence: 91%
“…This increase is not statically significant but indicates that there was no appreciable change in the joints' structural performance. However, the load-displacement curves exhibit a bi-linear response, reflecting a change in stiffness, and this behaviour is consistent with other published works on similar adhesive joints [33,19]. The second region with a lower slope can be attributed to the plastic deformation of the adhesive.…”
Section: Resultssupporting
confidence: 91%
“…It was one T of adhesives used by Kelly to experimentally show that the judicious choice of the adhesive leads to a higher static and fatigue strength of HBB joints [8]. Similar conclusions can be found in [7,[9][10], while numerous published papers showed higher mechanical performances can be obtained with HBB joints such as in [11][12][13][14][15][16][17][18][19][20][21][22] for example.…”
Section: Introductionsupporting
confidence: 60%
“…It was observed that the failure load increase with increasing the ratio of overlap length to adherend thickness. Bodjona et al [56] reviewed the hybrid bonded fastening joints and their applications in composite structures covering the experimental research, an analytical and numerical model of both joints, the design and manufacture of hybrid bonded bolted (HBB) joints and the hybrid bonded pinned (HBP) joint as detailed in Table 4.…”
Section: Adhesive Joint Failures In Compositesmentioning
confidence: 99%